2019
DOI: 10.3390/jcm8091377
|View full text |Cite
|
Sign up to set email alerts
|

DJ-1 in Parkinson’s Disease: Clinical Insights and Therapeutic Perspectives

Abstract: Mutations in the protein DJ-1 cause autosomal recessive forms of Parkinson’s disease (PD) and oxidized DJ-1 is found in the brains of idiopathic PD individuals. While several functions have been ascribed to DJ-1 (most notably protection from oxidative stress), its contribution to PD pathogenesis is not yet clear. Here we provide an overview of the clinical research to date on DJ-1 and the current state of knowledge regarding DJ-1 characterization in the human brain. The relevance of DJ-1 as a PD biomarker is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(93 citation statements)
references
References 88 publications
1
92
0
Order By: Relevance
“…One of the examples is the oxidative modification of the DJ-1 protein. The DJ-1 protein, which contains 189 amino acids, has been linked to PD because the loss of its functions causes disease with parkinsonian characteristics [55]. The oxidative modifications in a single amino acid of the DJ-1 protein are sufficient to favor PD development.…”
Section: Processed Meat Containing Oxidized Proteins Inmentioning
confidence: 99%
“…One of the examples is the oxidative modification of the DJ-1 protein. The DJ-1 protein, which contains 189 amino acids, has been linked to PD because the loss of its functions causes disease with parkinsonian characteristics [55]. The oxidative modifications in a single amino acid of the DJ-1 protein are sufficient to favor PD development.…”
Section: Processed Meat Containing Oxidized Proteins Inmentioning
confidence: 99%
“…Concerning VEGF, and it was already mentioned, this factor plays an important role in the neurorescuing of DAn, by interacting with different players in the potentiation of the dopaminergic system [52,54]. Similarly, it is DJ-1 that has been described as a major player and target for PD modeling and repair [2,55,56]. Notably, studies have demonstrated that DJ-1 deficiency sensitizes microglial cells to release pro-inflammatory cytokines (e.g.…”
Section: Discussionmentioning
confidence: 98%
“…Mechanistically, this promising HDAC inhibitor can up-regulate the protein deglycase (DJ-1). DJ-1 acts as a versatile prosurvival factor in DA activating different protective mechanisms such as regulation of mitochondria, antioxidative stress response, and up-regulating total intracellular glutathione in response to a diverse range of PD related insults (Repici and Giorgini, 2019 ).…”
Section: Neuroinflammation In Parkinson’s Diseasementioning
confidence: 99%